A 3D bioprinted in situ conjugated‐co‐fabricated scaffold for potential bone tissue engineering applications. Issue 5 (23rd January 2018) - Sithole, Mduduzi N.; Kumar, Pradeep; du Toit, Lisa C.; Marimuthu, Thashree; Choonara, Yahya E.; Pillay, Viness
Abstract: There is a demand for progressive approaches in bone tissue engineering to repair and regenerate bone defects resulting from trauma or disease. This investigation sought to engineer a single‐step in situ conjugated polymeric scaffold employing 3D printing technology as an innovative fabricating tool. A polymeric scaffold was engineered in situ employing sodium alginate as a bio‐ink which interacted with a poly(ethyleneimine) solution on bioprinting to form a polyelectrolyte complex through ionic bond formation. Silica gel was included in the bio‐ink as temporal inorganic support component and for ultimate enhancement of osteoinduction. Characterization of the biorelevant properties of the scaffold was undertaken via Fourier Transform Infrared Spectroscopy, Differential Scanning Calorimetry and Thermogravimentric Analysis, X‐Ray diffraction, Scanning Electron Microscopy, and biomechanical testing. The scaffold maintained its 3D architecture for the duration of the 28‐day degradation investigation, while potentially permitting the infiltration of nutrients, growth factor, and cells evident by the increased solvent penetration into the scaffold observed via Magnetic Resonance Imaging studies. The scaffold porosity and pore size were found to be 60% and 360 µm, respectively. Biomechanical evaluation revealed a Young's modulus of 18.37 MPa highlighting that the scaffold in its current form possesses the mechanical capabilities for certain bone tissue engineering applications. This investigation provided highlighted the applicability of alginate‐poly(ethyeneimine)/silica for 3D bioprinting as a scaffold which could possess potential as a bone tissue engineering scaffold. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1311–1321, 2018.